Pengembangan Model Pembelajaran Inquiri Dinterferensi Pendekatan Scientific untuk Meningkatkan Keterampilan Berpikir Ilmiah Siswa SMA - Jusniar Jusniar; Sumiati Side (ChemEdu, 2020)
The main objectives to be achieved from this research is to produce books Scientific learning model - Enquiry and supporting devices such as lesson plans, worksheets and valid assessment tools, practical and effective in improving students' scientific thinking skills. Instructional material used as the focus of this research is the solution of electrolyte and non-electrolyte that is presented in class X semester. Activity presents a real problem in the class is the first step of learning, so it is expected that students are able to analyze problems, hypothesize, collect the data and concluded through experimentation. This is not apart of the activities 5 M (Observe, ask, reasoning, Tried and Communicate) which is the scientific thinking activities of students. The development method used is Plomp (1997), which consists of four stages, namely; 1) The initial assessment by observation early in the school curriculum, the students and the state sylaby appropriate learning model; 2) planning draft of the model scientific - inquiry and materials suitable for development, 3) realization & Construction to develop the book model of scientific - inquiry together with learning devices namely lesson plans, worksheets and assessment tools skills of scientific thinking of students, while stage 4) implementation has not been done for I. year study the validity of test results from three experts to book models and devices obtained by each (book model = 3.23; RPP = 3.29; LKS = 3.19 and assessment tools = 3.10) total mean with a 3.20 average coefficient of expert judment index equal to one category is valid. Test the practicality of the model and the Scientific - Inquiry through perception questionnaires gained an average of 89.47% of students (32 students) who respond positively to the application of models and tools, and of the three chemistry teacher at SMAN 1 Bajeng average of 90.05% giving a positive response to the model and the device. Test the effectiveness evident from the test results show class completeness of 81.25% (26 students completed). Feasibility study can be seen from the observation of student activity associated with formulating problems, observe, ask questions, give argimen, formulate hypotheses, collect and data analyze, discuss, cooperation and conclude group average of 75.83%. Based on these two indicators show that the model and the device is effective to improve learning outcomes and scientific thinking skills.